2011
DOI: 10.1016/j.appet.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Food in the family. Bringing young people back in

Abstract: This article analyzes eating and beliefs about family meals in the qualitative interview narratives of 30 “at-risk” gang-involved young women in the San Francisco Bay Area. We begin our examination of consumption practices with a study of households and identify three major types–extended, single-parent and blended. Within these households, food purchasing and consumption activities are varied, and in many cases, our respondents rely upon extended family members and non-kin relations for support. In examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Despite these challenges, adolescents represent a crucial target group in which to improve food literacy because of the potential to influence family, peers, and short‐ and long‐term health. While adolescence is acknowledged as a time of independence, this age group does place value on family and household meals as having both social and emotional significance . There is also recognition of the role adolescents may play in influencing, purchasing and preparing meals in households .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, adolescents represent a crucial target group in which to improve food literacy because of the potential to influence family, peers, and short‐ and long‐term health. While adolescence is acknowledged as a time of independence, this age group does place value on family and household meals as having both social and emotional significance . There is also recognition of the role adolescents may play in influencing, purchasing and preparing meals in households .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to Croll, Neumark-Sztainer, and Story (2001), young people associate healthy food with fruit and vegetables, eaten in a situation “such as home” (p. 195) or together with the family. Hunt et al (2011) found that young people value family meals and that they like to be activated and involved in food-related activities; at the same time, they use food to create a life separate from their families, by trying to come to terms with their identity, security, and independence. Hunt et al (2011) also stated that even if there are situations in which family relationships are experienced as problematic, cooking and eating at home have positive significance in the lives of young people, indicating that there is a certain sense of congruency with constituent 2, especially in relation to significant others early in life (e.g., the family).…”
Section: Discussionmentioning
confidence: 99%
“…In general, a person's identity, in relation to his or her choice of diet, can be seen as being dependent on early experiences of food, in terms of trajectories, such as persistent thoughts, feelings, strategies, and actions (Bisogni, Jastran, Shen, & Devine, 2005; Devine, 2005; Devine, Connors, Bisogni, & Sobal, 1998). This makes the young adult's choice of a particular diet a way to connect and to belong to a certain social group as well (Fischler, 1988; Hunt, Fazio, MacKenzie, & Moloney, 2011). Therefore, choosing a lifestyle based upon an organic diet could suggest an opportunity to establish a sense of stability for the young adult, in terms of identity and belonging.…”
mentioning
confidence: 99%
“…| 179 bs_bs_banner PERSSON OSOWSKI and MATTSSON SYDNER has shown that a higher frequency of family meals is associated with children being of normal weight, having healthier diets and eating patterns, and a decreased likelihood of disordered eating (Hammons & Fiese, 2011). On the other hand, family meals have also been described as a declining event and as a contributor to dietary problems (Hunt, Fazio, MacKenzie, & Moloney, 2011). Here, social class plays a part.…”
mentioning
confidence: 99%